Pengaruh Penggunaan Media Komik terhadap Motivasi Belajar Siswa pada Mata Pelajaran IPS di SMP Islam Al-Azhar 37 Pekanbaru - Muhammad Al-Habib; Sakilah Sakilah (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study set out to measure how strongly the use of comic media shapes students' motivation to learn the Social Science (IPS) subject at Islam Al-Azhar 37 Junior High School in Pekanbaru. The issue behind it was students' faint drive to succeed together with instructional media that had failed to support their motivation. A quantitative route was taken via a quasi-experiment of the nonequivalent control group kind. From a population of 60 seventh graders, 19 students of class VII.C served as the experimental group and 19 of class VII.B as the control group, chosen through purposive sampling. Observation, questionnaires, and documentation gathered the data, which were then examined with normality, homogeneity, hypothesis (independent sample t-test), effect size, and N-Gain Score analyses run on SPSS Statistics 27. The findings established that comic media did shape students' motivation: the observed t of 3.156 outstripped the t-table value of 1.688 while the significance of 0.003 stayed under 0.05, leading Ha to be accepted and H0 rejected. The effect size of 0.512 (51.2%) sat in the moderate band, with the remaining 48.8% traceable to other factors.